The Study of Large-Scale Fading Using a Wavelet Transform Method - Guizhen Lu; Zhi Cao; Xingning Jia; Jingjing Liang (International Journal of Antennas and Propagation)
A wavelet method is proposed to evaluate the modeling of the first- and second-order statistics of large-scale fading from the signal strength measurement. The selection of wavelet is very important in using a wavelet method, and the steps of the wavelet method are given for the study of wave propagation loss. The path loss of measurement is analysed with different levels of wavelet decomposition and compared with an optimized Hata model. The correlation of slow fading on different scales shows that the correlation distance is related to the spatial scale.